An Evaluation of The Relationship Between Self-Reported Sleep/Awake Bruxism and The Chronotype Profiles of The Dental Students - Burcu Yılmaz; Halenur Bilir (Cumhuriyet University, 2022)
Objectives: The aim of this study is to evaluate the possible relationship between the presence/absence of the self-reported sleep and/or awake bruxism and the chronotype profiles of dental students. Materials and Methods: The dental students at Istanbul Medipol University and Istanbul Medeniyet University in the fall semester of the 2020-2021 academic year participated in this study. Along with demographic data, an 11-item questionnaire evaluating sleep quality and self-reported sleep and awake bruxism, and a 19-question Morningness-Eveningness Questionnaire (MEQ) determining the chronotypes were applied. The significance level was set at P≤ 0.05 for statistical analysis. Results: 171 students (female:128, 74.9%; male:43, 25.1%) participated in the study. The mean age was 22.32.2. There was no statistical difference between the presence or absence of the bruxism types and the chronotype profiles of the students (P=0.815). The sleep quality in the students with the sleep bruxism was statistically lower than in other types of the bruxism (P<0.05). The participants with the sleep bruxism were statistically more likely to have difficulty concentrating on the daily activities than the participants with other types of the bruxism (P<0.05). Conclusions: There is no relationship between the presence or absence of the bruxism types and the chronotype profiles. However, the sleep bruxism negatively affects both the sleep quality and focusing on the daily activities.